Gait training using a hybrid assistive limb (HAL) attenuates head drop: A case report. (June 2018) - Miura, Kousei; Koda, Masao; Kadone, Hideki; Kubota, Shigeki; Shimizu, Yukiyo; Kumagai, Hiroshi; Nagashima, Katsuya; Mataki, Kentaro; Fujii, Kengo; Noguchi, Hiroshi; Funayama, Toru; Abe, Tetsuya; et al.
Highlights: This is the first case report of using the HAL for dropped head syndrome (DHS). To date, there is no established conservative treatment method for DHS. In this case, gait training using the HAL dramatically ameliorated head drop. The HAL is a choice for the treatment of DHS in addition to previous methods. Abstract: Dropped head syndrome (DHS) is characterized by a chin-on-chest deformity, which can severely interfere with forward vision and impair activities of daily living. A standardized treatment strategy for DHS has not been established. To our knowledge, this is the first case report describing the efficacy of gait training using a hybrid assistive limb (HAL) for DHS. A 75-year-old man showed apparent head drop in a standing position, resulting in passively reducible chin-on-chest deformity. A radiograph image showed apparent cervical kyphosis. Center of gravity of the head (CGH)–C7 SVA was +115 mm, CL was −40°, and T1S 39°. The patient underwent a treatment program using HAL, in which gait training was mainly performed, 60 min a day, 5 days a week for 2 weeks (10 sessions). After 2–3 sessions, dropped head started to attenuate. At the end of 10 sessions, the patient was able to walk with normal posture and radiograph images showed cervical kyphosis dramatically decreased because of HAL training. CGH–C7 SVA was 42 mm, CL was −1.7°, and T1S was 30°. Three months' outpatient follow-up revealed a slight deterioration of cervical alignment. However, the patient was able to maintain a better cervical alignment than before HAL training and keep walking with forward vision. There were no complications in any HAL treatment session. In conclusion, gait training using HAL is an option for treatment of DHS in addition to previously reported neck extensor muscle training.